Public awareness of the field of speech-language pathology - Kerkez, Jelena; Milankov, Vesela; Radonjić, Jelena; Dumendžić, Andrea; Ćatović, Erna (Norma, 2025)
Speech-language therapists are specialists who focus on the prevention, detection, assessment, diagnosis, therapy, counseling, and scientific research of communication and swallowing disorders in individuals of all ages. While the speech therapy profession is legally recognized in the Republic of Serbia, its regulatory framework and institutional support are still insufficiently developed, and professionals in the field encounter a range of challenges. The main objective of this research is to examine public awareness of the field of speech therapy. The sample consisted of 207 respondents of various ages. For the purposes of this research, an online questionnaire was created and distributed via informal groups and social media. The majority of respondents indicated that they received most of their information about speech therapy from friends, and they also gathered information from personal experience. In addition, most respondents believed that children with articulation disorders are the most common users of speech therapy services, while a small number of respondents thought that children with fluency disorders require treatment. Most respondents believed that a child should be taken to a speech therapist if they have not spoken by 18 months of age, and it was proven that there is no statistically significant difference between the awareness of employees in institutions with and without a speech therapist, nor between respondents of different educational levels.
Keywords: speech-language therapist; profession; awareness; services; public